Analisis Pengendalian Mutu Dry Rubber Content (DRC) Menggunakan Metode Peta Control Chart di PT. SEMADAM - Ryan Pramanda; Wiky Sabardi; Dewiyana (Fakultas Teknik Universitas Samudra, 2021)
Dry Rubber Content (DRC) is used as a standard for production materials at PT Seumadam. Inaccurate DRC data may affect product quality. Determining the quality of DRC products aims to analyze quality standards to obtain the right, accurate, effective, and applicable method for use in the rubber sheet production process. Large plantations determined that DRC was not following the standard and only based on manual dry weight deviation of rubber. Determination of the quality of dry rubber that needs to be tested and adjusted to the needs of the rubber sheet industry so that the determination of the value of dry rubber content can be carried out effectively and accurately.